Presentation of functional, PPS and Hall's methods in comparison with other research on space quality = Prezentacja metod: funkcjonalnej, PPS i Hall'a na tle innych badań jakości przestrzeni - Kossak-Jagodzińska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The end of the twentieth century was a period in which the need for quality control was developing in all areas of life in post-industrial countries. The impulse for the development of numerous methods of evaluating the quality in architecture and construction was "Green Paper" and "Agenda 21" concerning the idea of sustainable development.
Keywords: jakość przestrzeni publicznej; przestrzeń publiczna; idea zrównoważonego rozwoju; metoda badawcza; public space quality; idea of sustainable development; research method